2017
DOI: 10.3803/enm.2017.32.3.375
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Index Using Soluble CD36 Is Associated with the Prevalence of Type 2 Diabetes Mellitus: Comparison Study with Triglyceride-Glucose Index

Abstract: BackgroundPlasma soluble cluster determinant 36 (sCD36) level is closely related with insulin resistance and atherosclerosis, but little is known whether it could be a surrogate for estimating risk of developing diabetes or not. To address this, we evaluated association between sCD36 index, the product of sCD36 and fasting plasma glucose (FPG), and the prevalence of type 2 diabetes mellitus (T2DM), and then compared with triglyceride-glucose (TyG) index which has been suggested simple index for insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The association with the risk of T2DM has also been described, but it was not independent of fasting glucose, insulin, or adiposity [ 76 , 79 ]. The sCD36 index proposed by Kim et al [ 80 ] seems to be a better marker of T2DM risk in the general population than the concentration of sCD36. It is calculated with concentrations of sCD36 and fasting glucose in plasma and is independent of other risk factors.…”
Section: Association Of Scd36 With Diabetes Mellitusmentioning
confidence: 99%
“…The association with the risk of T2DM has also been described, but it was not independent of fasting glucose, insulin, or adiposity [ 76 , 79 ]. The sCD36 index proposed by Kim et al [ 80 ] seems to be a better marker of T2DM risk in the general population than the concentration of sCD36. It is calculated with concentrations of sCD36 and fasting glucose in plasma and is independent of other risk factors.…”
Section: Association Of Scd36 With Diabetes Mellitusmentioning
confidence: 99%
“…( 33) found a stronger correlation of TyG than of HOMA-IR with arterial stiffness. Compared to hyperinsulinemic-euglycemic clamp, TyG was more accurate (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…TyG index, the product of fasting glucose and TG in the blood, has been proposed as a simple method for determining IR in healthy subjects [8,10]. The use of the HOMA-IR homeostasis model [11,12], the insulin suppression test [8], and the hyperinsulinemic-euglycemic clamp [11,12] suggested that the TyG index correlates with IR [13]. TyG indexes are reported to be elevated in T2DM patients compared to parameters in patients with prediabetes [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, although TG has been suggested to be an independent risk factor for DM, the TG level is strongly influenced by a high carbohydrate diet, alcohol consumption, and lifestyles such as exercise. However, due to its convenience and relatively low cost, TG measurements are widely conducted in clinical practice [13]. an LDL-C reduction to a mean of 82 mg/dL was accompanied by a 37% reduction in major cardiovascular events compared with placebo.…”
Section: Discussionmentioning
confidence: 99%